Severe antibody‐mediated transfusion‐related acute lung injury in an obstetric patient following transfusion of fresh frozen plasma from a non‐transfused male blood donor - Charlotte Nielsen Agergaard (Clinical Case Reports, 2021)
Abstract Transfusion‐Related Acute Lung Injury (TRALI) has been associated with neutrophil reacting antibodies in transfused blood products. We report a case of life‐threatening TRALI in an obstetric patient triggered by transfusion from a non‐transfused male blood donor. A residual risk of TRALI exist, even in a male‐only plasma setting.